Antibacterial effect of Bacillus subtilis extract on the growth of pathogenic bacteria and analyzed by GC-MS - سارة Al-Rubyee; Najwa Ibrahim (College of Education for Pure Sciences, 2022)
The antibacterial effect of three selected isolates of Bacillus subtilis (Sar1, Sar2, Sar3) was tested by the agar diffusion method, and the results showed that there was no inhibitory effect of these bacteria against the growth of pathogenic bacteria; Staphylococcus aureus, Staphylococcus haemolyticus Escherichia coli, and Pseudomonas aeruginosa, while the undiluted and half-diluted (200, 100, 50) mg/ml extracts, of the three cultures which are tested by the Agar Well Diffusion method, had varying inhibitory effects towards the growth of these five pathogenic bacteria and more effect on gram-positive compared to its effect on gram-negative bacteria. Through GC-MS detection of secondary metabolites of Bacillus subtilis (Sar1) extract, which were selected because they are identical to Bacillus subtilis bacteria contained in the standard GeneBank with a percentage of (95)%, it was found that they consist of (33) chemical substances according to the number of peaks produced. After injecting the extract into the GC device, and when this information was entered into the MS device, it was diagnosed by its names with the calculation of its molecular weight and the amount of area it occupies as a percentage within the used extract understudy.